Memory complaints, dementia, and neuropathology in older blacks and whites - Arvanitakis, Zoe; Leurgans, Sue E.; Fleischman, Debra A.; Schneider, Julie A.; Rajan, Kumar B.; Pruzin, Jeremy J.; Shah, Raj C.; Evans, Denis A.; Barnes, Lisa L.; Bennett, David A. (Annals of neurology, 2018)
Objective To determine relationships of memory complaints to cognitive function and decline, incident dementia, and neurodegenerative and other neuropathologies, as well as the population‐attributable risk for dementia in older black and white persons. Methods A total of 4,015 community‐based persons (28% black; 74% women; mean baseline age = 78 years) were enrolled in 1 of 4 longitudinal cohort studies, and another 2,937 in a population‐based cohort. Memory scores, assessed using 2 questions (5‐point Likert scales) were categorized as complaints present or absent. Global cognition and 5 cognitive domains were derived from annual neuropsychological tests. Dementia was assessed from these tests and additional data. Neuropathologic data were available for 1,350 deceased subjects with brain autopsies. Regression and mixed effects models were used to examine relationships of memory complaints to cognition and neuropathology. Results Baseline memory complaints (n = 1,310; 33% of 4,015) were associated with lower cognition and faster decline in all domains (global score estimate = −0.032, standard error = 0.004, p < 0.0001), during a mean follow‐up of 6 (standard deviation = 2) years. Persons with memory complaints had higher dementia risk (hazard ratio = 1.64, 95% confidence interval [CI] = 1.42–1.89) and odds of pathologic Alzheimer disease (odds ratio [OR] = 1.96, 95% CI = 1.51–2.54), neocortical Lewy bodies (OR = 2.47, 95% CI = 1.54–3.96), and other neurodegenerative pathologies. Results for dementia risk were similar among blacks and whites. Among 2,937 older persons in a population‐based cohort with similar data, the population‐attributable risk for incident dementia due to memory complaints was 14.0% (95% CI = 2.6–23.0), and did not vary between the black and white groups. Interpretation Memory complaints are common in older black and white persons, and relate to cognitive decline, dementia risk, and neurodegenerative pathologies. Ann Neurol 2018;83:718–729